Comparative Analysis of Daily Trust and Vanguard Newspapers’ Coverage of Political Parties in the 2023 Presidential Election in Nigeria - Yadima, Gaius Jeff (Darul Yasin Al Sys, 2024)
This study was conducted to assess how newspapers covered political parties, by comparing Daily Trust and Vanguard newspapers coverage of political parties in the 2023 presidential election in Nigeria, to find out the political party with the highest attention and the most common theme of coverage. The study adopted Agenda Setting Theory as the theoretical framework and content analysis as the research design. Data were collected with the aid of coding sheet as the instrument of data collection. Simple random sampling technique was adopted and weekly editions of the population of Daily Trust and Vanguard newspapers starting from 17th of October, 2022 to the 24th of February, 2023 were used for the study. Each day of the week was written down on a separate piece of paper from Monday to Sunday. The researcher randomly selected one paper to reveal the sampled days of the week which in turn was analyzed, 38 publications were analyzed. The data from these newspapers were analyzed using descriptive statistics. Findings revealed that out of the 18 political parties that participated in the 2023 presidential election, All Progressives Congress (APC) had the highest attention on the selected newspapers with Vanguard newspaper giving them more frequency than Daily Trust newspaper. It was also found out that, policy was the most common theme of coverage during the period of the presidential election in Vanguard newspaper than the Daily Trust newspaper. Based on these findings, it is recommended that Nigerian newspapers should endeavor to give equal attention, representation and coverage to all political parties during and after election as enshrined in the constitution.